2013
DOI: 10.1016/j.biortech.2013.09.114
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of rice husk addition on hydrothermal treatment of sewage sludge: Fate and environmental risk of heavy metals

Abstract: Hydrothermal treatment (HTT) at 200°C was applied to immobilize heavy metals (HMs) and the effect of rice husk (RH) addition was investigated based on total HMs concentration, fractionation and leaching tests. The results indicated that a synergistic effect of RH addition and HTT could be achieved on reducing the risk of HMs from medium and low risk to no risk. Metals were redistributed and transformed from weakly bounded state to stable state during the HTT process under RH addition. Notably at a RH/sludge ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(24 citation statements)
references
References 35 publications
(15 reference statements)
1
20
1
Order By: Relevance
“…found that there were synergistic positive effects on the fuel properties and air pollutant emissions in the thermal conversion process of both biomass and low‐rank coal because of the similar chemical molecular structure. Shi et al . demonstrated that heavy metals in SS may be stabilized during the HT process when rice husk is added to SS.…”
Section: Introductionmentioning
confidence: 99%
“…found that there were synergistic positive effects on the fuel properties and air pollutant emissions in the thermal conversion process of both biomass and low‐rank coal because of the similar chemical molecular structure. Shi et al . demonstrated that heavy metals in SS may be stabilized during the HT process when rice husk is added to SS.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the mobile and bioavailable heavy metal ion fractions were transformed into relatively stable fractions after pyrolysis and most of the heavy metal ions were found to exist in the residual form in the biochar pyrolyzed at 700 °C (Devi and Saroha, 2014). Similarly, Islam and Park, (2017) Shi et al (2013b) reported that the addition of rice husk during the hydrothermal treatment of sewage sludge exhibited a reduction effect on the leaching toxicity of heavy metals in sludge residues. It was observed that at the rice husk/sludge ratio of 1/1.75, the concentrations of leachable Cr, Ni, Cu, and Cd decreased by 17%, 89%, 95%, and 93% respectively.…”
Section: Co-pyrolysismentioning
confidence: 99%
“…Some of the oil properties such as HHV and carbon content were found to be improved by co-pyrolysis (Q. . Some efforts have been made to investigate the cumulative effect of biomass addition on lowering the contamination risk of heavy metals in sewage sludge residues (H. Jin et al, 2017;Shi et al, 2013b). However, there has been limited research investigating co-pyrolysis effect of oily sludge and sawdust on heavy metal immobilization.…”
Section: Summary Of Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations